(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This article presents the results of an experimental forensic medical study of scalp wounds caused by the edges of sharp and blunt objects. The relevance of the study is обусловлена by the high prevalence of chopped and lacerated-contused head injuries in forensic medical practice, as well as by the need to improve diagnostic criteria for identifying the injuring instrument.